ANALISIS KELAYAKAN USAHATANI SALAK (Salacca edulis) DI KECAMATAN BELITANG II KABUPATEN OGAN KOMERING ULU TIMUR - Syahril Haris, Munajat (JASEP, 2025)
Salak is one of the horticultural commodities that has the potential to be developed commercially and oriented towards agribusiness. This study aims to analyze the income and feasibility of salak farming. The study was conducted in Belitang II District, East OKU Regency, where the research location was determined intentionally. The research method used was the survey method. While the sampling method used in this study was the census method. The data processing method used the income formula and RC ratio. The results showed that the income of salak farming in Belitang II District, East OKU Regency was Rp 98,815,887.00/year. Salak farming in Belitang II District, East OKU Regency is feasible to be cultivated, with an R/C value of 4.16 or > 1.